An expectation-based memory deficit in aging - Bollinger, Jacob (2011)
Memory performance can be enhanced by expectations regarding the appearance of ensuing stimuli. Here, we investigated the influence of stimulus-category expectation on memory performance in aging, and used fMRI to explore age-related alterations in associated neural mechanisms. Unlike younger adults, who demonstrated both working memory (WM) and long-term memory (LTM) performance benefits for face stimuli when this stimulus category was expected, older adults did not exhibit these memory benefits. Concordantly, older adults did not exhibit expectation-period activity modulation in visual association cortex (i.e., fusiform face area (FFA)). However, within the older population, individuals who demonstrated face-expectation memory benefits also exhibited expectation-period FFA activity modulation equivalent to younger adults. The older cohort also displayed diminished expectation-related functional connectivity between regions of the prefrontal cortex and the FFA, relative to younger adults, suggesting that network alterations underlie the absence of expectation-mediated cortical modulation and memory benefits. This deficit may have broader consequences for the effective utilization of predictive cues to guide attention and engender optimal cognitive performance in older individuals.